Risk factors for progression of chronic kidney disease in children with nephrotic syndrome - Adrian, Riki; Sovira, Nora; Haris, Syafruddin; Andid, Rusdi; Darnifayanti, Darnifayanti; Yusuf, Sulaiman (Indonesian Pediatric Society, 2025)
Background Nephrotic Syndrome (NS) is a progressive kidney disease in children that can lead to chronic kidney disease (CKD). Understanding the interactions between various risk factors is critical in developing new strategies to prevent the progression of CKD in pediatric patients with NS. Objective To determine the risk factors for the progression of CKD in children with nephrotic syndrome at Dr. Zainoel Abidin Public Hospital, Banda Aceh. Methods This analytical observational study with a cross-sectional approach was conducted from September 2021 to September 2023. Data were obtained from medical records of 52 children aged 2 to 18 years in the inpatient and outpatient wards of Dr. Zainoel Abidin Public Hospital, Banda Aceh who met the inclusion criteria. Bivariate analysis using the Chi-square and Fisher's tests and multivariate analysis using logistic regression test were performed. Results Of 52 subjects, most were male and over ten years of age; 53.8% of subjects had Stage 1 CKD. The majority of stage 3-5 of CKD cases had immunosuppressive toxicity and anemia, while the majority of all subjects had hyperfiltration and proteinuria. Risk factors for CKD progression in children with NS are Hypertension (OR 2.54; 95%CI 0.32 to 20.1; P=0.003), immunosuppressant toxicity with (OR 33.67; 95%CI 2.59 to 437.5; P=0.007) and anemia (OR 33.92; 95%CI 2.77 to 414.5; P=0.006). Conclusion Hypertension, immunosuppressant toxicity and anemia for CKD progression in children with NS.